Characterization of two large duplications of F9 associated with mild and severe haemophilia B, respectively. Issue 3 (13th March 2019) - Xie, Xiaoling; Chen, Changming; Liang, Qian; Wu, Xi; Wang, Xuefeng; Wu, Wenman; Ding, Qiulan
Abstract : Introduction: Only two large duplications of F9 causing haemophilia B (HB) have been reported. Aim: To analyse the pathogenic mechanisms of large F9 duplications. Methods: We have identified two large duplications of F9 (dup ex 1‐6 and dup ex 4‐6) associated with mild and severe HB in probands A and B, respectively. Here, we localized the breakpoints of the two duplications using long‐range PCR and genome walking combined with quantitative primer walking strategies. We traced the origin of dup ex 4‐6 by haplotype analysis then performed somatic mosaicism detection in sporadic pedigree B and detected the effect of chimeric intron derived from the duplication on transcription by minigene assay. Results: Mechanisms of fork stalling and template switching and/or microhomology‐mediated break‐induced replication (FoSTeS/MMBIR) might be responsible for the formation of two tandem direct duplications. The dup ex 4‐6 was traced to maternal grandmother of proband B, who was both somatic mosaicism and germline mosaic and the duplication might be formed during mitosis of her early embryonic cells. Minigene assay demonstrated that chimeric intron generated three transcripts, one minor transcript produced an in‐frame protein adding duplicated 143 amino acids into the normal FIX, explaining the small amount of larger FIX shown in Western blot. The inter‐ F9 dup ex 1‐6 adjacent to the original F9 copy created two identical promoters, and promoter competition might be the pathogenic mechanism of the duplication causing mild HB. Conclusions: This study highlights that duplications can be associated with diseases by complicated pathogenic mechanisms.